PENGARUH PEMBIAYAAN MUSYARAKAH, MARKET SHARE DAN MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Ayu Yunita; Meutia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
The purpose of this research is to examine the influence of musyarakah financing, market share, and intellectual capital to financial performance on islamic commercial banks in Indonesia in 2013-2018. The research type used is verificative research by using Purposive sampling method. The target population of this research are 14 islamic commercial banks in Indonesia and the sample of the research are islamic commercial banks. The data used in this research are secondary data, which are gotten from for the book year ended December 31, 2013, 2014, 2015, 2016, 2017, and 2018. The result of this research show that musyarakah financing, market share, and intellectual capital silmutaneously influence to financial performance. Partially, musyarakah financing has influence to financial performance, market share has influence to financial performance, and intellectual capital has influence to financial performance.